HSP90 multi-functionality in cancer - Albakova, Zarema (Frontiers in Immunology, 2024)
The 90-kDa heat shock proteins (HSP90s) are molecular chaperones essential for folding, unfolding, degradation and activity of a wide range of client proteins. HSP90s and their cognate co-chaperones are subject to various post-translational modifications, functional consequences of which are not fully understood in cancer. Intracellular and extracellular HSP90 family members (HSP90α, HSP90β, GRP94 and TRAP1) promote cancer by sustaining various hallmarks of cancer, including cell death resistance, replicative immortality, tumor immunity, angiogenesis, invasion and metastasis. Given the importance of HSP90 in tumor progression, various inhibitors and HSP90-based vaccines were developed for the treatment of cancer. Further understanding of HSP90 functions in cancer may provide new opportunities and novel therapeutic strategies for the treatment of cancer.